Perlindungan Hukum bagi Konsumen Jasa Perjalanan Wisata - Jazzar Jazzar; Sri Handajani (Syntax Corporation Indonesia, 2025)
Legal protection for consumers of travel services is a crucial issue in the tourism industry, especially in cases of traffic accidents that cause consumer losses. This study aims to analyze the legal liability of travel service providers based on the Civil Code, Consumer Protection Law, and other relevant regulations. The findings indicate that in cases of traffic accidents, business operators can be held accountable under Articles 1365 and 1367 of the Civil Code, which regulate unlawful acts and employer liability for subordinates. Additionally, accident victims are entitled to compensation from PT Asuransi Jasa Raharja under the provisions of Law No. 34 of 1964. Dispute resolution can be pursued through litigation and non-litigation channels, including the Consumer Dispute Settlement Agency (BPSK). These regulations are expected to ensure adequate legal protection for consumers in the use of travel services.